Машинне навчання з використанням хмарних обчислень - Кучков, Б. О. (ХНУРЕ, 2023)
The given work discusses the long-term machine learning model using cloud computing. Designing a machine learning methodology in the cloud. Solving problems related to memory and limiting script execution by established cloud technology providers. Method for Executing Sequential Lamba Functions on AWS with Intermediate Results Stored in AWS EFS